Effectiveness of Cyclic Voltammetry in Evaluation of the Synergistic Effect of Phenolic and Amino Acids Compounds on Antioxidant Activity: Optimization of Electrochemical Parameters - María José Jara-Palacios; Emilio Begines; Francisco J. Heredia; María Luisa Escudero-Gilete; Dolores Hernanz (Foods, 2024)
Antioxidant activity can be evaluated using cyclic voltammetry (CV). The aim of this work is to verify the efficacy of CV in evaluating the synergistic effect of bioactive compounds, such as phenolic and amino acid compounds, on antioxidant activity. Therefore, three types of model solutions were prepared: individual model solution (phenol and amino acid), (b) binary model solutions (phenol-phenol and amino acid-amino acid) and (c) mixed phenol–amino acid solutions. Electrochemical measurement conditions were optimized for phenolic compounds (pH 3.0, 1.0 g/L and 100 mV/s) and for amino acids (pH 7.0, 2.0 g/L for amino acids and 100 mV/s), and, for each solution, the functional groups responsible of the anodic and cathodic peaks were established. The peak anodic potential (Epa) and the onset potential (Eon) were two parameters of great importance. The first one was used to classify the solutions according to their antioxidant potential. In general, all the binary and mixed solutions had lower values of Epa than the corresponding individual model solution, which indicates an improvement in the antioxidant potential. The second one was used to evaluate the synergistic effects of phenolic compounds and amino acids.